Association between soy products and prostate cancer: A systematic review and meta-analysis of observational studies - Yiping Huang; Wenyan Wang; Jianxiang Jin (Investigative and Clinical Urology)
Purpose: The effect of soy products on prostate cancer (PCA) remains a topic of debate. This study aimed to investigate the association between soy products consumption and the incidence of PCA. Materials and Methods: A search was conducted in the PubMed, EBSCO, Web of Science, and Cochrane Library databases up to December 2023. The adjusted odds ratio (OR) and corresponding 95% confidence interval (CI) were used to assess the association. Results: A total of 22 articles, comprising 1,409,213 participants, were included for this meta-analysis. The results indicate that soy products reduce the risk of PCA (OR=0.94, 95% CI=0.91–0.97, p<0.001), especially in cases of localized or low-grade PCA (OR=0.94, 95% CI=0.90–0.97, p<0.001), but exhibit no effect on non-localized or high-grade PCA (OR=0.96, 95% CI=0.91–1.01, p=0.085). Furthermore, increased consumption frequency was negatively associated with PCA risk. Specifically, soy products can reduce the risk of PCA in African Americans (OR=0.89, p=0.006) and Latinos (OR=0.93, p=0.036), but have no impact on Japanese (OR=0.99, p=0.655), Chinese (OR=0.90, p=0.155), and Whites (OR=0.96, p=0.133). Non-fermented soy products were associated with a reduction in the incidence rate of PCA (OR=0.93, 95% CI=0.90–0.96, p<0.001), while fermented soy products had no effect on the incidence rate of PCA (OR=1.10, 95% CI=0.98–1.22, p=0.096). Conclusions: The consumption of soy products can reduce the overall risk of PCA among men. Various factors, including soy products-related factors (e.g., consumption, frequency), population-related factors (e.g., race), and PCA-related factors (e.g., PCA stage) collectively influence the effect of soy products on PCA.